Experience and outcomes of a theatre intervention for youth on probation and their university peers - Fullcharge, Aileen (Applied psychology in criminal justice, 2018)
This study examined the qualitative impact of a unique theatrical partnership, The Odyssey Project, between a university and a probation camp facility for boys. Seven youths who committed criminal offenses and seven university students were brought together as peers and mentored daily by university faculty for six weeks. They participated in structured theatrical activities that culminated in a public performance of an adaptation of the Homeric epic poem The Odyssey. Observations, interviews, and questionnaires investigated participants' experiences and interpretations of class activities including why they joined, how they interpreted their experiences, and what impact the program had on them. Results suggest that a psychologically safe space was created by clear expectations and boundaries, positive regard shown to participants, and distress-reducing mindfulness activities, which allowed the participants to feel comfortable enough to share and be vulnerable. Program processes and outcomes are discussed along with limitations and future directions.